Community Ability In The Process Of Transporting Emergency Victims Due To Traffic Accidents - Purnamasari, Vela; Wahyu Tanoto (Chakra Brahmanda Lentera Institute, 2023)
Background: Traffic accidents are unintentional incidents on the road that can result in casualties. Accident victims must be immediately moved to a safer place with the right process. The ability of a rescuer to carry out the process of transportation and relocation will greatly affect the victim's condition. This study aims to determine the community's ability in the transportation process transfer of accident victims in Bendo Village, Pare District, Kedir Regency. Method: The research design uses descriptive. The research population is 259 respondents, and the sample is 26 respondents. The research technique is purposive sampling, and the single variable is the community's ability to transport accident victims in Bendo Village, Pare District. The research instrument uses observation. Data analysis uses the percentage formula and is interpreted quantitatively. Results: The research results from 26 respondents showed that a small number had sufficient ability, 6 respondents (23%), and almost all respondents had less ability, 20 respondents (77%). Conclusion: The ability of the community in the process of transportation for the transfer of accident victims is influenced by age, educational background, gender, marital status, occupation, living status with family, how often they help accident victims, and whether or not they have received information about emergencies before. It is hoped that the community will be able to apply the transportation process for moving accident victims appropriately to minimize more serious injuries to the victims. In this case, researchers can socialize to increase the community's ability to the transportation process for moving accident victims.